Implementación de una lente de alta ganancia basada en estructuras metálicas iluminadas por una guía de onda circular. - Orozco Castillo, Juan Pablo (2024)
This research project focuses on implementing and analyzing a dual-band metallic lens composed of several rings of different diameters. The proposed antenna is based on /2 and /4 resonators, and a circular waveguide feeder covering the two bands of interest is designed. To achieve the main objective of implementing the dual-band metallic lens operating at 2.4 GHz and 5 GHz, the electromagnetic simulator CST Studio Suite is utilized. This software allows modeling and simulating the antenna behavior. Additionally, Altair Feko is used to employ the characteristic mode theory to examine the propagation modes and their power contribution. This approach facilitates adjusting the design to achieve the desired behavior in the target bands, considering parameters such as gain, directivity, efficiency, reflection coefficient, and radiation pattern. Moreover, the plane wave incidence method is used to find the appropriate focal point to place the feeder relative to the lens. The proposed lens is made of 0.65 mm thick copper and is placed on foam with a relative permittivity of 1.053. It consists of a central ring and 12 coplanar rings symmetrically distributed every 30 degrees around the central ring. For the feeder, 0.45 mm thick aluminum is used throughout its structure. A small support with a threaded rod is placed for coupling between the lens and the feeder to fix the lens onto the feeder. The results obtained from the CST Studio Suite electromagnetic simulator demonstrate that the proposed lens meets the expected operating parameters. An adaptation for both frequencies exceeding -10 dB for the reflection coefficient is observed. Additionally, an increase of 2.48 dB in directivity is recorded in the 2.4 GHz band, and a 2.56 dB increase is observed in the 5 GHz band.